Predicting the predictor's variables of survival time for oral cancer with decision tree analysis - Wan Ahmad, Wan Muhamad Amir; Mohd Ibrahim, Mohamad Shafiq; Rohim, Rabiatul Adawiyah; Ali, Zalila (Institute of Advanced Science Extension (IASE), 2018)
Decision tree analysis is one of the famous analyses which assist the researcher to identify the associated factor that contributes to the certainty factor. In this study, we proposed a decision tree model with the high-risk factor and try to estimates the importance of every each predictor. The result reveals that the survival time for the patient is mostly depending on nerve invasion and the size of a tumor, followed by alcohol and ethnicity factor. This promising technique had led to a successful research and give the best results for the decision making especially for the decision maker. In conclusion, this analysis can provide a very useful for forecasting the survival time (in months) of oral cancer patients.